Comparative of The Law Enforcement Systems for Rape Against Women in Indonesia and India - Septiani, Altiah; Albab, Ulil (Universitas Muhammadiyah Malang, 2024)
The aim of this research is to understand the legal system between Indonesia and India and what preventive measures are in place for the high rate of crimes involving the rape of women. Even though it is clear what the forms and types of punishment in both countries are based on the Criminal Code, with the increasing number of rapes what are the steps for courts and judges to pass sentences on perpetrators of rape and efforts to prevent them. The urgency of this writing and research is to answer how the English and Roman legal systems compare. The research method used is normative (Legal Research) and other data sources, namely primary legal sources listed such as Law Number 39 of 1999, Law Number 65 of 2005, Law Number 12 of 2022, Indonesian Criminal Code, Indian Criminal Code, Indian National Commission Act 1990, Indian Criminal Law Amendment 2013 and Indian Criminal Law Amendment 2018. The novelty of this research is the explanation of enforcement with differences in rape legal systems. The results of this research are that the enforcement of rape law in Indonesia is that judges are not bound by anything and anyone in handing down decisions (Inquisitorial) and are based on the Criminal Code (Codification), whereas India takes previous judges' decisions in similar cases in higher courts (Precedent) with presenting several legal experts (Doctrine) and making the Criminal Code a source of law (Statute). Indonesia's preventive efforts include establishing the National Commission on Violence Against Women and passing the TPKS Law. Meanwhile, the Indian state formed a National Commission for women with the involvement of Indian women activists to fight rape.